UPAYA PENINGKATAN AKTIFITAS DAN PRESTASI BELAJAR BIOLOGI SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI SMPN 5 KOTA BENGKULU - JULIARTI JULIARTI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to increase student activity and achievement in class VIII biology at SMP Negeri 5 Bengkulu City for the 2021/2022 academic year. This type of research is classroom action research (PTK) which has been carried out in three cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The subjects in this study were class VIIIB students at SMP Negeri 5 Bengkulu City for the 2021/2022 academic year. The objects in this research are student activities, teacher activities and student achievement. Data collection techniques in this study are in the form of tests and non-tests (observation). Data analysis used descriptive analysis techniques. The data obtained in this study were implementation data of lesson plans (teacher activities), student activity data and learning achievement tests. Based on the research results, it was obtained that the percentage of implementation of lesson plans in cycles I, II and III was 100%, including the category